A lei moral em Kant e a crítica de Anscombe à ética de leis - Lopes, Malaquias Augusto (2021)
This dissertation presents the moral law in Kant and Anscombe's objections regarding the conception of moral obligation within the ethics of principles. According to Anscombe the concepts of moral obligation in modernity trace back to a secularized conception of ethics grounded in divine law, which loses its theological support in Modernity. Therefore, in the absence of this conception, moral concepts of obligation are vague, devoid of descriptive content, and should be discarded. Within this framework of criticism, Kantian ethics was directly cited, specifically with regard to the concept of self-legislation and universalizable maxims. As a way of contrasting Anscombe's criticism of the Kantian moral theory, Korsgaard's responses to Anscombe are inserted in the present debate. In defense of a Kantian moral theory, Korsgaard brings in her argument the perspective of the agent-centered view to counter Anscombe's criticism of the Kantian concept of self-legislation. As a hypothesis, we will try to demonstrate that even though Anscombe's criticism may be strong, it does not compromise the Kantian moral system.